(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article considers the successive link of the ideas of «virtuous city» of Al-Farabi with modernity. «Virtuous city» manager, in the universal sense, outside the time framework, burdened by the weight of responsibility for every citizen, for his worthy life. In this direction he undertakes serious steps and makes preventive decisions. The article of President of the Republic of Kazakhstan N.A. Nazarbayev «Social modernization of Kazakhstan: 20 steps to the Society of Universal Labour» – this is a strategic step of the head to the achievement of all benefi ts for the worthy life of citizens. The author presented the vision about a role of creating work in society; the main mechanisms of realization of objectives in this program document are presented. Keywords: «virtuous city», head, social modernization, labour, religious studies.